Morphological, morphometric and meristic characteristics of larvae of altum angelfish (Pterophyllum altum) (Pellegrin, 1903) and management of its first feeding (Orinoquia, 2014)
The altum angelfish is a representative species of the South American ichthyofauna due to it`s wide acceptability in the aquarium`s market, making it a species with great productive potential. In this study, a morphological description, detail of meristic parameters during its first life stages and aspects of first feeding were evaluated. Ten broodstock couples were kept in 50 L aquariums with aeration and constant temperature. After the breeding, 15 larvae/h were collected every hour until 75 hours post-hatching (HPH) and fixed in 4% buffered formalin for the analysis of the meristic and morphological characteristics. Likewise, different diets with Artemia salina nauplii (T1), capsulated Artemia salina cyst (T2) and wild zooplankton (T3) were offered to the larvae to determine some productive aspects. The P. altum larvae has cylindrical and rounded body, elongated tail and an ovoid yolk sac which is evident until it`s development as post-larvae. Regarding its morphometric characteristics, the larvae had a total length of 4.64±0.5 mm, standard length of 3.8±0.2 mm, eye diameter of 0.49±0.2 mm, head length of 0.71±0.8 mm and body height of 0.76±0.6 mm at 75 HPH. No significant differences between treatments were observed in the final weight (P>0.05); however, differences in the specific growth rate and in the survival were observed (P
Keywords: Live food; morphological characteristics; growth; fish; zooplankton